Design and development of dairy products enriched with polyunsaturated fats - Vargas, Jorge (2017)
The goal of this work has been to design and develop products such as fresh cheese and yogurt, enriched with polyunsaturated fatty acids. Fresh milk was used as raw material and soybean oil as source of polyunsaturated fatty acids. The content of polyunsaturated fatty acids in fresh cheese made from skim milk enriched with 2 to 4% soybean oil, increased from 5.01% to 54.83%. Similarly, the content of polyunsaturated fatty acids in natural yogurt made from skim milk enriched with 1 to 3% soybean oil, increased from 4.28% to 54.98%. We conclude that is feasible to produce dairy products enriched with polyunsaturated fatty acids and their manufacture is recommended.